Perbandingan Pendekatan Restorative Justice dan Sistem Peradilan Konvensional dalam Penanganan Kasus Pidana - Flora, Henny Saida (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research aims to compare restorative justice and conventional justice systems in the handling of criminal cases. In this context, it can be understood to comprehend the differences, similarities, and the impact of both approaches in the context of law enforcement and criminal justice. A qualitative approach is employed to gain a deep understanding of the characteristics, similarities, and differences between the two approaches in a practical context. Research data is obtained through in-depth interviews with actors involved in the criminal justice system, such as judges, prosecutors, law enforcement officers, social workers, offenders, and victims. The results of this research depict similarities in the focus on achieving justice and community protection between both approaches. However, fundamental differences emerge in their primary goals, with Restorative Justice emphasizing reconciliation, recovery, and conflict resolution, while the conventional justice system tends to lean more towards punishment as a form of retribution. The Restorative Justice approach assigns a more active role to victims in the process of handling criminal cases, enabling them to speak and participate in the recovery process. Meanwhile, the conventional justice system often follows a formal and adversarial process. This research has significant implications for understanding how both approaches can contribute to achieving fair and effective justice goals. The results of this research can be used as a basis for formulating better policies in handling criminal cases.